Fundamental analysis : an application on Singapore Airlines Limited - Koh, Tee Boon (2015)
The boom in the local stock market has sent prices of many stocks through the roof, to exorbitant levels which would intimidate many value investors. Amid this optimism in the market, the stocks of some companies, however, have not performed satisfactorily. Do these companies have investment values? Their true value can be uncovered through an application of fundamental analysis. Through this appraisal process, one would be able to understand the environment in which each company operates in and evaluate its attractiveness against other similar companies. We have chosen to apply the concepts of fundamental analysis on Singapore Airlines Limited, which is the most profitable company in the world airline industry. Its admirable performance (despite operating out of a small domestic base) must be a result of its own merits, which warrants a thorough study. We do not attempt to determine a fair price for investment purposes, but rather to ascertain the outlook and prospects of this remarkable company. Over the following report, we first review the world economic outlook, which greatly affects the airline industry. The industry study examines the key factors underlying the general profitability of airlines. We then take a closer look at the company, and illustrate its past performances and prospects in the near term. We also attempt to forecast its profit for the financial year ending March 1994. The final section makes some comparisons with other regional airlines. We have gone quite a bit into details but we believe that this is worthwhile as we see the company as a rose among the thorns in the ailing airline industry. We certainly have benefited in this process by putting into practice the equity analysis concepts learnt in the Financial Analysis course. We have realised that there is no definite way in analysing a company. This process takes a lot of judgment on the part of the analysts . It undoubtedly requires a lot of practice to improve one's skills in the area of fundamental analysis . We sincerely hope that our research efforts will spur more final year projects of this nature in the future .